Analisis Perilaku Kerja Prestatif dalam Perspektif Al-Qur'an - Waryainah, Waryainah (ojs.unsiq.ac.id, 2022)
Achievement Work Behavior is one of the work attitudes that need to be applied by workers, namely where a worker always has the ambition to move forward (ambition drive). Whereas in the Qur'an Allah has arranged all human affairs in such a way as to serve as a guideline as well as regarding achievement work behavior. This is what became interesting until the author took the title of the research